Whose Golden Age? Some Thoughts on Jewish-Christian Relations in Medieval Iberia - Ray, Jonathan (Studies in Christian-Jewish Relations, 2011)
The medieval period in Spanish history has alternately been cast as a Golden Age of interfaith harmony and an example of the ultimate incompatibility of Muslim, Christian, and Jewish communities. In this essay, I suggest that a better way to understand interfaith relations in medieval Iberia is to think about these religious communities in less monolithic terms. With regard to Jewish-Christian relations in particular, factors such as wealth, social standing, and intellectual interests were as important as religious identity in shaping the complex bonds between Christians and Jews.